Ruang Lingkung Studi Islam - Darwis, Ahmad; Sultani, Dalmi Iskandar; Dewi, Azzahra Kusuma (Melati Institute, 2025)
The research aims to find out how the scope of Islamic studies. Using literature study, by examining various sources of relevant classical and contemporary literature. The result of this study is that Islam does not only regulate human relationships with God, but also regulates life in socio-politics. The conclusion of this research is that Islamic studies must be understood in depth in order to be able to answer the various challenges of the times and contribute significantly.